the SHIFT OF LEXICAL COHESION IN TRANSLATION OF THE NOVEL THE ADVENTURES OF SHERLOCK HOLMES - astari, nyoman yuli (Lingual Journal of Language and Culture, 2019)
Abstract        This paper aims to describe the translation equivalent of the lexical cohesion found in The Adventure s of Sherlock Holmes ; and to identify the effects of shift of cohesion in translation of “ The Adventure s of Sherlock Holmes “ and its translation. In this paper qualitative descriptive method is used to describe or analyze the data of shift of cohesion in translation. The finding shows that the lexical cohesion in the text is built by a number of repetition, synonymy, near-synonymy, superordinate, general word and collocation. Shifts of cohesion found in the novel are shifts in the level of explicitness and shifts in the textual meaning(s). Shifts in the level of explicitness; i.e. the general level of the target texts’ textual explicitness is higher or lower than that of the source text and Shifts in the textual meaning(s); i.e. the explicit and implicit meaning potential of the source text changes through translations.   Key words: lexical cohesion, translation strategy, and shift of cohesion.